2020
DOI: 10.1002/jmri.27438
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Spin Labeling Applications in Pediatric and Adult Neurologic Disorders

Abstract: Arterial spin labeling (ASL) is a powerful noncontrast magnetic resonance imaging (MRI) technique that enables quantitative evaluation of brain perfusion. To optimize the clinical and research utilization of ASL, radiologists and physicists must understand the technical considerations and age-related variations in normal and disease states. We discuss advanced applications of ASL across the lifespan, with example cases from children and adults covering a wide variety of pathologies. Through literature review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 99 publications
1
43
0
Order By: Relevance
“…The results of ASL are consistent with PET and DSC, and ASL provides a brain CBF measurement with high reliability and repeatability [16,17]. Pseudo-continuous ASL (PCASL) can be used for whole-brain scanning and has a high clinical application value [14,15,18,19]. Most studies confirmed the detection of cerebral hypoperfusion in the acute phase of aura followed by rebound hyperperfusion [20,21] and hyperperfusion in the onset phase [22][23][24].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The results of ASL are consistent with PET and DSC, and ASL provides a brain CBF measurement with high reliability and repeatability [16,17]. Pseudo-continuous ASL (PCASL) can be used for whole-brain scanning and has a high clinical application value [14,15,18,19]. Most studies confirmed the detection of cerebral hypoperfusion in the acute phase of aura followed by rebound hyperperfusion [20,21] and hyperperfusion in the onset phase [22][23][24].…”
Section: Introductionsupporting
confidence: 59%
“…Research on perfusion imaging include the widely applied techniques of positron emission tomography (PET), CT perfusion, single photonemission computed tomography (SPECT), dynamic susceptibility contrast (DSC), magnetic resonance perfusion imaging and perfusion-weighted imaging (PWI) [11][12][13]. One of the non-invasive cerebral perfusion imaging techniques is arterial spin labeling (ASL), that can be utilized to quantitatively assess the degree of cerebral perfusion without having to apply a gadolinium-based contrast agent [14,15]. The results of ASL are consistent with PET and DSC, and ASL provides a brain CBF measurement with high reliability and repeatability [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…MR angiography sequences provide insight into the integrity of the vascular anatomy either by the use of intravenous contrast to enhance blood signal, by designing sequences to manipulate the blood signal relative to be much darker than other tissue (black-blood), much brighter (bright-blood) (Nakao et al, 2018), or by introducing flow-sensitive encoding (phase-contrast) (Pelc, Bernstein, Shimakawa, & Glover, 1991). Arterial spin labeling quantitatively and noninvasively estimates brain perfusion with arterial blood water (Bambach, Smith, Morris, Campeau, & Ho, 2020; Telischak, Detre, & Zaharchuk, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research on perfusion imaging include the widely applied techniques of positron emission tomography (PET), CT perfusion, single photon-emission computed tomography (SPECT), dynamic susceptibility contrast (DSC), magnetic resonance perfusion imaging and perfusion-weighted imaging (PWI) [11][12][13]. One of the non-invasive cerebral perfusion imaging techniques is arterial spin labeling (ASL), that can be utilized to quantitatively assess the degree of cerebral perfusion without having to apply a gadolinium-based contrast agent [14,15]. The results of ASL are consistent with PET and DSC, and ASL provides a brain CBF measurement with high reliability and repeatability [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This method adopts a fast spin echo sequence and helically lls the K space with higher resolution. It can be used for whole-brain scanning and has a high clinical application value [14,15,18,19]. Due to its hybrid nature, PCASL is the most commonly used sequence in modern ASL imaging [18,19].…”
Section: Introductionmentioning
confidence: 99%